2017
DOI: 10.1007/s00330-017-5061-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of single-kidney glomerular filtration rate (GFR) with CT urography versus renal dynamic imaging Gates method

Abstract: • A new CT method can assess split renal function • Only using images from CT urography and the value of haematocrit • A one-stop-shop CT technique without additional radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
1
7
0
3
Order By: Relevance
“…Kwon et al, reported that unilateral GFR measured by contrast enhanced CT was reproducible and it agreed well with the iothalamate clearance [22]. An additional article by You et al reported that, with a renal dynamic image as the reference, the unilateral renal GFR measured by CT revealed a well and significant correlation [23]. We have found similar results in the current study, especially for patients with modified eGFR over 60 mL/min.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Kwon et al, reported that unilateral GFR measured by contrast enhanced CT was reproducible and it agreed well with the iothalamate clearance [22]. An additional article by You et al reported that, with a renal dynamic image as the reference, the unilateral renal GFR measured by CT revealed a well and significant correlation [23]. We have found similar results in the current study, especially for patients with modified eGFR over 60 mL/min.…”
Section: Discussionsupporting
confidence: 88%
“…It measures objective renal depth while also providing information of renal location and morphology, and, thus, it helps to raise the accuracy when evaluating the GFR. The multidetector CT had been used to measure unilateral renal GFR [22,23]. Kwon et al, reported that unilateral GFR measured by contrast enhanced CT was reproducible and it agreed well with the iothalamate clearance [22].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the product of kidney volume and CT enhancement value may be used for evaluating kidney function. 36 Hence, spiral CT is a reliable tool to determine whether the contrast agent is filtered by the kidney. Renal blood perfusion and renal filtration effect the CT enhancement at different stages, and have different effects on renal CT value.…”
Section: Imaging Methodsmentioning
confidence: 99%
“…Renal blood perfusion and renal filtration effect the CT enhancement at different stages, and have different effects on renal CT value. 35 , 36 Therefore, contrast media can cause renal injury, which limits the application of enhanced CT.. The accuracy of kidney function by the CT enhancement scan remains to be improved.…”
Section: Imaging Methodsmentioning
confidence: 99%
“…[1] Glomerular filtration rate (GFR) is the most direct indicator which can reflect renal filtering function, and it is also one of the most sensitive indicators which are used to evaluate renal function. [2] However, GFR can be only acquired indirectly by calculating the clearance rate of some markers instead of being measured directly. Inulin clearance rate is a generallyacknowledged golden standard in GFR measurement, but it is not suitable to be popularized in clinical practice due to its complicated operation and time waste.…”
Section: Introductionmentioning
confidence: 99%